Pengembangan Media Pembelajaran berbasis Flash Card untuk Meningkatkan Hasil belajar Siswa Kelas V - Supriyaddin, Supriyaddin; Hasan, Hasan; Budiman, Budiman; Rahman, Arif (Jurnal Evaluasi dan Kajian Strategis Pendidikan Dasar, 2024)
This research is motivated by the limited use of learning media which reduces the effectiveness of learning in class, so that students do not understand the material. This research offers the development of new media in the form of flash cards that are appropriate to the concrete operational stage, with the aim of improving student learning outcomes. The aim of this research is to test the validity, practicality and effectiveness of flash card media on the learning outcomes of class V students at Madrasah Ibtidaiyah (MI) Al-Mujahidin. This research uses research and development methods with the ADDIE model. Data collection techniques include interviews, observation, tests, and documentation. Data analysis techniques include analysis of validity, practicality and media effectiveness. Validation results by two experts show that learning media has a validity level of 87% (very valid). The practicality of flash card media reaches 93% (very practical). Students' cognitive learning results show a classical completion level of 91%. In the affective aspect, 24% of students were in the "Very Good" category, 64% in the "Good" category, and 9% in the "Quite Good" category. In the psychomotor aspect, 67% of students were in the "Good" category and 36% were in the "Fairly Good" category.